ESL Students' Reflective 'Burning Experiences' at a Writing Workshop - Buripakdi, Adcharawan (EAST WEST JOURNAL OF HUMANITIES, 2011)
Writing workshops can become a site of igniting a genuine passion for writing. This paper explores how writing workshops can be used to empower and liberate students. It describes the experiences of graduate students in writing a personal book. Grounded in a narrative research approach, this study is a description of ESL students' reflective ' Burning Experiences' at a writing workshop held in a graduate class in the United States. Based on personal interviews and ethnographic observations, a Thai student narrated her experiences and those of her thirteen classmates from seven countries toward the creative writing project in the workshop. Findings reveal that sharing stories that students were "burning to write" allowed them to get rid of the 'I can't write syndrome'. These students also felt empowered, were freed of constraints, and found their own voices. Most importantly, the writing workshop was a site where students used writing not simply as a tool but also as forum to express their real identity. Finally, the compelling experiences in this writing class included the negotiation of writers' roles, the discovery, exploration and identity negotiation and construction. This study provides teachers an alternative way of teaching ESL composition.